A heterotrophic nitrification and aerobic denitrification strain Acinetobacter sp. MLW2301 - Jianfeng, Gao; Halim, Murni; Mohamed, Mohd Shamzi; Mohamad, Rosfarizan (The Korean Society for Mocrobiology / The Korean Society of Virology, 2025)
Heterotrophic nitrification aerobic denitrification are biological process for treating wastewater. Its purpose is to remove nitrogen from wastewater, such as nitrite or nitrate. The key to these processes lie in selecting strains with high efficiency in heterotrophic nitrification and aerobic denitrification, and studying their cultivation and application conditions. In this study, Acinetobacter sp. strain MLW2301 was isolated from the lake water and sediment of Mines Lake, Selangor, Malaysia. This strain exhibits strong heterotrophic nitrification and aerobic denitrification abilities, effectively decomposing nitrate and nitrite in wastewater. By optimizing the culture conditions, the biomass reached 8.12 × 109 CFU/ml after 8 h under conditions of pH 7.0, 35℃, and 300 rpm. In the application condition optimization tests, the strain demonstrated optimal nitrite and nitrate removal efficiency at 28.05℃, pH 6.45, and 270.48 rpm. The removal rates for nitrite and nitrate were 65.13% and 78.26%, corresponding to 2.61 mg/L/h and 3.13 mg/L/h, respectively. Temperature was found to be a significant factor while all the other pairwise interactions were insignificant. The MLW2301 strain shows strong nitrogen removal capabilities, making it effective in purifying water by removing nitrate and nitrite from wastewater. It holds significant commercial potential for practical applications.